Management In A New Perspective (In Comparative Study Literature) - Hernawati W. Retno Wiratih; M. Havidz Aima; Alfadli Santowijaya; Hermanto Harun; Muhammad Ridwan (Greenation International Journal of Tourism and Management, 2023)
Management Science has been in existence and evolving for about 3,000 years, spanning three distinct eras: prehistoric, historical, and modern. It's evident that knowledge of management is an integral part of human existence. In this article, we aim to introduce a novel perspective on Management, emphasizing the idea that effective management begins with self-mastery before extending to external management endeavors. The approach taken in this article involves merging established management theories with principles from the Alqur'an, Hadith, and works like "The 7 Habits of Highly Effective People," "Maximum Achievement," and "Kubik Leadership." Management, in essence, is defined as the art of collaborating with people and utilizing organizational resources to accomplish predefined objectives. In simpler words, it's about employing resources to achieve set goals through effective interactions with people. Islamic teachings emphasize two main purposes for human creation: worshiping the Creator and acting as stewards or natural managers (others management). When fulfilling the role of steward or nature manager, Islamic teachings stress the significance of self-management as a foundation for behavior. This concept is mirrored in the principle of sidiq (fairness), which forms a trust-building self-mirror, ultimately leading to self-growth. The Seven Habits, as presented by Covey, provide guidelines for high effectiveness, emphasizing the importance of personal mastery. Conclusion of this article emphasizing before managing external aspects of one's life and environment through established management theories, it is essential to begin by nurturing oneself. This process involves drawing inspiration from the teachings of the Alqur'an and Hadith, as well as other referenced literature mentioned within this article.